Role of Inflammatory Mediators in Chronic Obstructive Pulmonary Disease Pathogenesis: Updates and Perspectives - Pankush; Khushboo Bharti; Rohit Pandey; Namita Srivastava; Shashank Kashyap; Deepak Kumar; Lokender Kumar; Sunil K. Suman; Sanjay K. S. Patel (Immuno, 2025)
Chronic obstructive pulmonary disease (COPD) is a chronic, debilitating condition that affects the lungs and airways. It is characterized by persistent bronchitis, a condition exemplified by the inflammation of the bronchial tubes, the hypersecretion of mucus, emphysema, and the destruction of the airway parenchyma. The combination of these conditions leads to persistent tissue damage, pulmonary fibrosis, and ongoing inflammation of the airways. The inflammatory response in COPD is a complex process that is orchestrated by a wide range of immune cells. These include lung epithelial cells, monocytes, macrophages, neutrophils, eosinophils, and T and B lymphocytes, among others. These cells work together to produce a wide range of inflammatory biomarkers that are involved in the pathogenesis of COPD. Some of the key inflammatory biomarkers that have been identified in COPD include a variety of cytokines, the C-reactive protein/serum albumin ratio, fibrinogen, soluble receptor for advanced glycation endproducts, club/clara cells in the lungs with a molecular weight of 16 kDa, surfactant protein D, adiponectin, reactive oxygen species, and proteases. This review aims to provide a comprehensive overview of the role of immune cells and key inflammatory biomarkers in the development and progression of COPD. It will delve into the intricacies of the inflammatory response in COPD, exploring the various cell types and biomarkers that are involved in this process. By understanding the underlying mechanisms that drive COPD, we can better develop targeted treatments that can help to alleviate the symptoms of COPD.